2014
DOI: 10.1038/aps.2014.53
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of novel aromatase inhibitors using a homogeneous time-resolved fluorescence assay

Abstract: Aim: aromatase is an important target for drugs to treat hormone-dependent diseases, including breast cancer. The aim of this study was to develop a homogeneous time-resolved fluorescence (HTRF) aromatase assay suitable for high-throughput screening (HTS). Methods: A 384-well aromatase HTRF assay was established, and used to screen about 7000 compounds from a compound library. Anti-proliferation activity of the hit was evaluated using alamarBlue(R) assay in a hormone-dependent breast cancer cell line T47D. Mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…However, another dietary flavonoid, hesperitin increased the expression of aromatase at the mRNA level suggesting that dietary flavonoids could regulate aromatase expression differentially [65]. The results of a high-throughput study screening of 7000 compounds identified an imidazolyl quinoline derivative of flavonoids with aromatase inhibitor effect at a concentration of 0.81 µM decreasing the proliferation of T47D breast cancer cells [66]. Based on the structure of isoflavanones a new class of aromatase inhibitors has been developed with the ability to inhibit aromatase activity in the concentration range of 0.26 to 5.8 µM [67].…”
Section: In Vitro Effect Of Polyphenolsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, another dietary flavonoid, hesperitin increased the expression of aromatase at the mRNA level suggesting that dietary flavonoids could regulate aromatase expression differentially [65]. The results of a high-throughput study screening of 7000 compounds identified an imidazolyl quinoline derivative of flavonoids with aromatase inhibitor effect at a concentration of 0.81 µM decreasing the proliferation of T47D breast cancer cells [66]. Based on the structure of isoflavanones a new class of aromatase inhibitors has been developed with the ability to inhibit aromatase activity in the concentration range of 0.26 to 5.8 µM [67].…”
Section: In Vitro Effect Of Polyphenolsmentioning
confidence: 99%
“…Androgens (androstendione and testosterone) are converted to estrogens (estrone and estradiol) by aromatase; estradiol enters the nucleus and binds to estrogen receptors (ER) which interacts with estrogen response elements (ERE) triggering cell proliferation. So far, luteolin, flavonoid and isoflavonoid derivatives have been found to inhibit aromatase activity in breast cancer cells [64,66,67].…”
Section: In Vitro Effect Of Polyphenolsmentioning
confidence: 99%
“…This resulted in the formation a hydrogen bond with the important residue Arg115. It was earlier established that the involvement of the residues Agr115 and Ser478 were noticed with the natural flavonoid compounds as aromatase inhibitors [42] thereby illuminates the potentially of FSK [43].…”
Section: Discussionmentioning
confidence: 99%
“…Aromatase activity is markedly inhibited by luteolin [ 266 ], but is up-regulated by hesperetin (3′,5,7-trihydroxy-4-methoxyflavanone) [ 265 ]. The imidazolyl quinoline derivative of flavonoids, XHN27, a potent aromatase inhibitor, significantly suppresses the proliferation of breast cancer T47D cells, determined after screening a library of 7000 compounds [ 267 ].…”
Section: Anti-cancer Activity Of Polyphenols Against Breast Cancermentioning
confidence: 99%